A Simple Staircase Modulation for A Cascaded H-bridge Multilevel Inverter (University of Khartoum Engineering Journal, 2022)
This paper proposes a novel simple staircase modulation to obtain reasonable performance of an output voltage for a cascaded HBridgemultilevel inverter. The motivation of the proposed algorithm is that the inverter phase voltage intersects with an original sinusoidalwaveform at equal points in the y-axis. This modulation technique can calculate the independent switching angles more simply than thetraditional method, which employed Fourier’s series analysis, and can be applied to all kinds of multilevel inverters. In this paper, for the sake of validation, the technique was applied to a cascaded H-bridge inverter with unequal DC sources. Then, it was applied to the seventh, ninth, eleventh, and twenty-seventh levels of the multilevel inverter. In addition, pulse width modulation techniques used in this type of multilevel inverter are complicated. The PSIM software program was used for all simulation examples, and its results are consistent with the experimental results.